Performance Description Of Counselor Family Planning In The Implementation Family Planning Program In Demak District - Siti Istiana; Siti Nurjanah (Universitas Muhammadiyah Semarang, 2016)
Abstract.One of the problems in the management of family planning programs is still high unmet need. Unmet need isthe pair of fertile age who need family planning service are not met. The impact of these conditions it will be too close distance pregnancies (<2 year) which is one of the indirect cause of maternal mortality. In 2014 from a total of as much as 278.732 that fell into the unmet need of 22.627 or 8.12%. The main reason women of fertile age not using contraception that is most is they require a more in-depth explanation of contraceptive methods (29.4 %). On the other side, BAPERMAS already empowers counselor of family planning to socialize about contraception but the results have not been maximal .Purpose: This study aims to describe the performance of counselor family planning in the implementation of family planning programs. Method: quantitative study using cross sectional approach. Respondents are counselor family planning some 65 people in the district. Data was collected through interviews using aquestionnaire. Data analysis techniques by univariate analysis.Results: showed that the characteristic respondents (29-51 years of age, had an average of 4 village built, mostly already qualified higher education (DIII/ DIV/SI/S2) and working>10 years). Total of 53 respondents to approach the formal leaders, 36 respondents collection data and mapping, 55respondents to approach informal leader, 53 respondents development of the agreement. Total of 55 respondents stabilization agreement, 34 respondents givecounseling, information and education, 48 respondents formed a grouppioneers, 57 respondents planning services . Total of 64 respondents provide information and coaching participants and38 respondents do recording, reporting and evaluation. Conclusion:for BAPERMAS in Demak District increase the number of counselor family planning,hold training for recording and reporting the latest format, continuity guidance from Ka.UPT, develop creativity counseling and proportional divison of duties.